'Being on the move': Time-spatial organisation and mobility in a mobile preschool. (June 2015) - Gustafson, Katarina; van der Burgt, Danielle
Highlights: We critically investigate the implications of a preschool practice on a bus. Combining theories of time-spatial organisation and mobility. The social order of the mobile preschool is structured by 'being on the move'. Logistics and choice of location prevailing over daily planning. Creating time and space for embodied habits. Abstract: The mobile preschool, a form of preschool practice in a bus, is a new and growing phenomenon in Swedish preschool education. Combining theories of time-spatial organisation and mobility, we critically investigate the implications of transforming traditional stationary preschool practice into a mobile preschool. Our findings show that the social order of the mobile preschool is 'being on the move' and that the travelling shapes the time-spatial organisation, with major implications for daily routines and activities. In our analyses we show how constant travelling characterises the mobile preschool as a social practice with (i) logistics and choice of place prevailing over daily planning, (ii) creation of time and space for embodied habits, (iii) teachers as attendants and children as passengers, and (iv) walking in lines. However, mobility and time-spatial constraints are also co-constructed and intimately connected with the participants' agency, since both children and teachers are actively 'doing time' and 'creating space' within the dominant structure of 'being on the move'.